Efeito antinociceptivo da toxina PnTx4(6-1), isolada do veneno da aranha Phoneutria nigriventer (Keyserling, 1891) - Bruna Luiza Emerich Magalhães (2013)
The venom of the “armed” spider Phoneutria nigriventer has several biologically active components including peptides, proteins, amino acids, salts etc. The symptoms resulting from this animal’s bite comprise local pain, arousal, salivation, lacrimation, priapism, seizures and spastic and flaccid paralysis of the anterior and posterior limbs. The toxin PnTx4(6-1), isolated from the PhTx4 fraction of these venom, is a single chain polypeptide composed of 48 amino acid residues, with a mass of 5244.6 Da. This polypeptide was initially described as a neurotoxin insecticide. PnTx4(6-1) appears to bind to site 3 of sodium channels in nerve cord synaptosomes of cockroach (Periplaneta americana) and slow down inactivation of sodium current in isolated axon of insect, without affecting sodium channels of skeletal muscle (rSKM1) and brain (rBIIA), both of rats. This result corroborated previous assays in which the intracerebral injection of the toxin (up to 30μg) in mice caused no apparent toxicity. The present study evaluated the antinociceptive effect of the PnTx4(6-1) in three experimental pain models, using the test paw withdrawal, subjected to compression (Randall & Selitto, 1957). The hyperalgesia in inflammatory pain model was caused by intraplantar injection of 250 μg of carrageenan. When administered in the same place, after an interval of two hours and thirty minutes, PnTx4(6-1) (5 μg) was able to restore the nociceptive threshold of the animals. The hyperalgesia in nociceptive pain model, was evoked by intraplantar injection of 2 μg of prostaglandin E2 (PGE2). The central administration of PnTx4(6-1) by intrathecal injection caused a dose-dependent antinociceptive effect against the hyperalgesia induced by PGE2. Briefly, a dose of 100 pmoles was able to raise the nociceptive threshold of the paw of rats, and the doses of 200 and 400 pmoles totally reversed the hyperalgesic effect evoked by PGE2, with duration of 30 minutes. The measurements in the contralateral paw revealed that PnTx4(6-1), when centrally administered, does not alter the nociceptive threshold of the paw untreated. Concerning to the neuropathic pain model the toxin (100 pmoles) reversed, lasting ten minutes, the hyperalgesia evoked by constriction of the sciatic nerve. This research with PnTx4(6-1) indicates a strong therapeutic potential to this molecule as a possible model to new analgesic.